Effect of cadmium chloride on the melanophores of Channa striatus (Bloch) - Radhakrishnan, M V; Hemalatha, S; Paul, V I (Indian Journal of Fisheries, 2011)
Sublethal effects of cadmium chloride (10 ppm. 10% of 96 h LC50) on themelanophores of Channa striatus was investigated to understand its toxicity onmelanophore morphology. Observed toxicopathological alterations includestatistically significant variations in the number, size and shape of the melanophors.Due to the lysis of the melanophores, the melanin contents are pouredinto the surrounding matrix of the connective tissue, between 20 and 30 days ofexposure. The cadmium induced morphological changes in the melanophores seemto be an attempt by the organism to protect the delicate epidermis from the toxicmedium. In addition to the physiological colour changes, there occurs slowmorphological colour changes also as evidenced by the gradual regeneration of thechromatophores. The density of chromatophores is maximum after 45 days. Theregenerated pigment cells were smaller in size and more in number when comparedwith the normal melanophores. The present study also shows a melanizing effectagainst cadmium toxicity.